Assessment of Innovative Technologies and Their Readiness for Remote Sensing-Based Estimation of Forest Carbon Stocks and Dynamics - World Bank (World Bank, Washington, DC, 2021)
In 2005, the parties to the United Nations Framework Convention on Climate Change (UNFCCC) began to formally set up a framework for financially incentivizing emissions reduction due to deforestation and forest degradation through conservation, the sustainable management of forests, and enhancement of forest carbon (C) stocks in developing countries. Forest-related greenhouse gas (GHG) emissions, emission reductions, and enhanced removals (carbon sequestration) are estimated by measurement, reporting, and verification (MRV) systems, usually based on a combination of remote sensing data, field or in situ measurements, and modeling approaches. Under the UNFCCC, the lack of consistency limits the comparability between countries and makes the reconciliation of national reports and global estimates that are needed for the 2023 Global Stocktake under the Paris Agreements difficult. Moreover, the ongoing costs of MRV systems can be high, while the accuracy of the estimates is often low, and thus not able to unlock the full potential of climate finance. In this context, the World Bank launched a study to assess the readiness of various innovative technologies. The study began with a review of the current and potential innovative technologies in order to gain a comprehensive understanding of the readiness of these technologies, and the challenges to rolling out their implementation. As a result, a set of the main technological challenges, and recommendations for overcoming them, were identified.